Investigation on Annealed Behaviour in the Powder of Cerium Oxide Nanostructures - Sathyaseelan, B; Anbarasu, V; Manigandan, A; Sivakumar, K (International Journal of Chemistry and Materials Research, 2014)
In this study, CeO2 nanoparticles were synthesized by a microwave-assisted method. The samples were characterized by X-ray diffraction (XRD), Transmission electron microscopy (TEM), Brunauer–Emmett–Teller method and UV- visible spectroscopy. Results show that the annealed temperature significantly affected the crystalline nature, particle size, and optical properties of the processed CeO2 nanoparticles. The XRD spectra indicate that the CeO2 crystal has a pure cubic structure. TEM images agreement with the XRD data shown that the average size of the nanoparticles. The optical properties of the samples are investigated by measuring the UV-VIS absorption at room temperature. With increasing annealed temperature the band gap of the samples remains almost same, and the size of the particles increases.